Low f‐Number Diffraction‐Limited Pancharatnam–Berry Microlenses Enabled by Plasmonic Photopatterning of Liquid Crystal Polymers. Issue 18 (25th March 2019) - Jiang, Miao; Guo, Yubing; Yu, Hao; Zhou, Ziyuan; Turiv, Taras; Lavrentovich, Oleg D.; Wei, Qi‐Huo
Abstract: Microlenses are desired by a wide range of industrial applications while it is always challenging to make them with diffraction‐limited quality. Here, it is shown that high‐quality microlenses based on Pancharatnam–Berry (PB) phases can be made with liquid crystal polymers by using a plasmonic photopatterning technique. Based on the generalized Snell's law for the PB phases, PB microlenses with a range of focal lengths and f ‐numbers are designed and fabricated and their point‐spread functions and ability to image micrometer‐sized particles are carefully characterized. The results show that these PB microlenses with f ‐number down to 2 are all diffraction‐limited. The capability of arraying these PB microlenses with 100% filling factor with a step‐and‐flash approach is further demonstrated. Abstract : Microlenses are indispensable optical components in numerous applications. It is shown that high‐quality microlenses and microlens arrays can be designed based on Pancharatnam–Berry phases and fabricated with liquid crystal polymers by using a plasmonic photopatterning technique. These microlenses are diffraction‐limited and are expected to find various unique applications such as microscopic imaging.